Pulmonary rehabilitation in bronchiectasis: a propensity-matched study. Issue 1 (17th January 2019) - Patel, Suhani; Cole, Aaron D.; Nolan, Claire M.; Barker, Ruth E.; Jones, Sarah E.; Kon, Samantha; Cairn, Julius; Loebinger, Michael; Wilson, Robert; Man, William D-C.
International guidelines recommend pulmonary rehabilitation for patients with bronchiectasis, supported by small trials and data extrapolated from chronic obstructive pulmonary disease (COPD). However, it is unknown whether real-life data on completion rates and response to pulmonary rehabilitation are similar between patients with bronchiectasis and COPD. Using propensity score matching, 213 consecutive patients with bronchiectasis referred for a supervised pulmonary rehabilitation programme were matched 1:1 with a control group of 213 patients with COPD. Completion rates, change in incremental shuttle walk (ISW) distance and change in Chronic Respiratory Disease Questionnaire (CRQ) score with pulmonary rehabilitation were compared between groups. Completion rate was the same in both groups (74%). Improvements in ISW distance and most domains of the CRQ with pulmonary rehabilitation were similar between the bronchiectasis and COPD groups (ISW distance: 70 versus 63 m; CRQ-Dyspnoea: 4.8 versus 5.3; CRQ-Emotional Function: 3.5 versus 4.6; CRQ-Mastery: 2.3 versus 2.9; all p>0.20). However, improvements in CRQ-Fatigue with pulmonary rehabilitation were greater in the COPD group (bronchiectasis 2.1 versus COPD 3.3; p=0.02). In a real-life, propensity-matched control study, patients with bronchiectasis show similar completion rates and improvements in exercise and health status outcomes as patients with COPD. This supports the routine clinical provision of pulmonary rehabilitation to patients with bronchiectasis. Patients with bronchiectasis benefit from pulmonary rehabilitation to the same extent as do patients with COPD, other than in the Fatigue domain of the CRQ. Patients with bronchiectasis should be referred for pulmonary rehabilitation. http://ow.ly/fQua30mOlPw